Development of an aversive Pavlovian-to-instrumental transfer task in rat - Campese, Vincent; McCue, Margaret; Lazaro-Munoz, Gabriel; LeDoux, Joseph; Cain, Christopher (Frontiers in Behavioral Neuroscience, 2013)
Pavlovian-to-instrumental transfer (PIT) is an effect whereby a classically conditioned stimulus (CS) enhances ongoing instrumental responding. PIT has been extensively studied with appetitive conditioning but barely at all with aversive conditioning. Although it's been argued that conditioned suppression is a form of aversive PIT, this effect is fundamentally different from appetitive PIT because the CS suppresses, instead of facilitates, responding. Five experiments investigated the importance of a variety of factors on aversive PIT in a rodent Sidman avoidance paradigm in which ongoing shuttling behavior (unsignaled active avoidance or USAA) was facilitated by an aversive CS. Experiment 1 demonstrated a basic PIT effect. Experiment 2 found that a moderate amount of USAA extinction produces the strongest PIT with shuttling rates best at around 2 responses per minute prior to the CS. Experiment 3 tested a protocol in which the USAA behavior was required to reach the 2-response per minute mark in order to trigger the CS presentation and found that this produced robust and reliable PIT. Experiment 4 found that the Pavlovian conditioning US intensity was not a major determinant of PIT strength. Experiment 5 demonstrated that if the CS and US were not explicitly paired during Pavlovian conditioning, PIT did not occur, showing that CS-US learning is required. Together, these studies demonstrate a robust, reliable and stable aversive PIT effect that is amenable to analysis of neural circuitry.